Implementasi E-Learning Pada Mata Pelajaran Jurusan IPA Menerapkan Pengembangan Waterfall - Azhari, Irvan; Yusda, Riki Andri; Rohminatin, Rohminatin (Forum Kerjasama Pendidikan Tinggi, 2022)
Student activity can be carried out by utilizing interactive technology and easy to use by students. E-Learning is learning that utilizes electronic media such as the internet, interactive TV and audio to deliver learning materials anywhere and anytime. In research conducted at MAS Alamanaar PTPN IV Pulu Raja, several things became obstacles in the learning process, including the limitations of learning resources based on computer and telecommunications technology. Materials that are applicable or applied should train students more but lack facilities and infrastructure, learning is still normative. Students need broad access to learning, active, creative, and a challenging learning environment. The use of the internet has not been optimal in finding learning resources. The lack of interest and interest of students in participating in learning the subjects of the IA (Natural Science) Department using conventional methods so far, which is indicated to be in line with the low student learning outcomes. Especially during a pandemic like today, schools need learning media that can be done online. Based on these problems, to support the learning process in schools, an E-Learning platform was built that can help schools in learning the IA (Natural Sciences) Department, because the features in E-Learning really help teachers and students in doing online learning, such as features materials, assignments, discussions between students and subject teachers and final grades that can be seen directly by students. The application is built using the SDLC Waterfall Model. The research method used is a qualitative method, with interview data collection techniques, observation and literature study. The results of this study, E-Learning can facilitate teachers and students for teaching and learning activities, practice questions and can overcome obstacles to teaching and learning activities, so that the E-Learning system is feasible to be implemented as a means of supporting learning in schools.